2021
DOI: 10.1103/physrevmaterials.5.075601
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and following T1 events in dry foams from geometric features

Abstract: Machine learning techniques have been recently applied in predicting deformation in amorphous materials. In this study, we extract structural features around liquid film vertices from images of flowing 2D foam and apply a multilayer perceptron to predict local yielding. We evaluate their importance in the description of the T1 events and show that a high level of predictability may be achieved using well-chosen combinations of features as the prediction data. The most relevant features are extracted by perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Previously [ 13 , 24 ], the value of was obtained based on manual measurements “by eye”, which is a time-consuming process responsible for large errors in calculations. Several methods are used to detect T1 events, including the use of neural networks [ 25 , 26 ]. Here, we propose a simple algorithm to obtain based on a purely statistical approach.…”
Section: Methodsmentioning
confidence: 99%
“…Previously [ 13 , 24 ], the value of was obtained based on manual measurements “by eye”, which is a time-consuming process responsible for large errors in calculations. Several methods are used to detect T1 events, including the use of neural networks [ 25 , 26 ]. Here, we propose a simple algorithm to obtain based on a purely statistical approach.…”
Section: Methodsmentioning
confidence: 99%
“…These events are also present in bulk materials as shown by studies investigating acoustic signals emitted by these avalanches [6][7][8][9][10]. In amorphous solids and foams deformation is characterized by similar fluctuations and the irreversible units of plasticity are shear transformation zones [11,12], and T1 events [13][14][15], respectively. Based on this accumulated knowledge one may conclude that all these heterogeneous materials exhibit substantially analogous, stochastic plastic behavior.…”
mentioning
confidence: 88%
“…When the liquid fraction is low, foams are referred to as being in a dry state. In a dry state, the bubble shape is polyhedral and local bubble rearrangement is induced by T1 events [25][26][27]. It has also been revealed that the local mobility of bubbles changes sharply around φ = 0.045 in quasi-two-dimensional foams confined between two plates [15].…”
Section: Introductionmentioning
confidence: 99%